PENGARUH BIAYA OPERASIONAL, BIAYA PRODUKSI DAN PENJUALAN TERHADAP LABA BERSIH - Rozi, Ainur; Bahri, Syaiful (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2023)
The study aims to analyze the effect of operating costs, production costs and sales on net profit. Net profit is the profit obtained from the amount of income deduction with tax withholding expenses. The research population is manufacturing entities in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange in 2019-2021. Non probability sampling technique with purposive sampling method with total data 57. Multiple regression analysis is a research data analysis technique. The results showed that operating costs negatively affect net income, meaning that high operating costs have an effect on reducing the value of net profit. Production costs do not affect net profit and sales have a positive effect on net income. Future research is expected to enlarge the scope of observations so that the results obtained are more general and applicable to many business sectors.